Satellite monitoring to prevent impact of drought on crop production: meteorological drought - CGIAR Research Program on Maize (2020)
Meteorological indices can be used as substitutes for AIs. We discuss meteorological indexes and review SL approaches that are suitable for predicting drought based on historical satellite data.